EFFECTIVENESS SONDONG CAPTURE TOOL IN THE VILLAGE BAKAU ACEH DISTRICTS MANDAH DISTRICT INDRAGIRI HILIR RIAU PROVINCE - Salendra Samsirjon; Irwandi Sofyan; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in June 2015 in the village of Bakau Aceh Mandah Indragiri Hilir District of Riau Province . The method used is a survey method that is by observation immediately see the spaciousness of fishing activities sondong. Data collected by direct down spaciousness by carrying out arrests and conduct interviews with fishermen sondong . The purpose of this study was to assess the effectiveness of the fishing gear bag sondong to catch. The calculations show that the volume of the bag unknown sondong 452 160 cm3 while total catch of 1.42 kg in 11 times ( setting) .From the above data , the calculation of the value of the bag sondong far from effective in accordance with the volume being stored in a bag.Keywords : Effectiveness , Pockets Sondong , Total Catch